A new in vitro muscle contraction model and its application for analysis of mTORC1 signaling in combination with contraction and beta-hydroxy-beta-methylbutyrate administration. Issue 10 (3rd October 2019) - Sato, Satoko; Nomura, Mitsuru; Yamana, Ikko; Uchiyama, Akira; Furuichi, Yasuro; Manabe, Yasuko; Fujii, Nobuharu L
ABSTRACT: Several food constituents augment exercise-induced muscle strength improvement; however, the detailed mechanism underlying these combined effects is unknown because of the lack of a cultured cell model for evaluating the contraction-induced muscle protein synthesis level. Here, we aimed to establish a new in vitro muscle contraction model for analyzing the activation of mammalian target of rapamycin complex 1 (mTORC1) signaling. We adopted the tetanic electric stimulation of 50 V at 100 Hz for 10 min in L6.C11 myotubes. Akt, ERK1/2, and p70S6K phosphorylation increased significantly after electrical pulse stimulation (EPS), compared to untreated cells. Next, we used this model to analyze mTORC1 signaling in combination with exercise and beta-hydroxy-beta-methylbutyrate (HMB), an l -leucine metabolite. p70S6K phosphorylation increased significantly in the EPS+HMB group compared to that in the EPS-alone group. These findings show that our model could be used to analyze mTORC1 signaling and that HMB enhances muscle contraction-activated mTORC1 signaling. Graphical abstract: : Experimental set-up of a new in vitro muscle contraction model for analysis of the activation of mTORC1 signaling pathway in cultured L6.C11 myotubes.